Awareness and impact of New York City's graphic point-of-sale tobacco health warning signs. Issue Volume 22:Issue e1(2013) (23rd June 2012) - Coady, Micaela H; Chan, Christina A; Auer, Kari; Farley, Shannon M; Kilgore, Elizabeth A; Kansagra, Susan M
Abstract : Background: To increase knowledge of smoking-related health risks and provide smoking cessation information at the point of sale, in 2009, New York City required the posting of graphic point-of-sale tobacco health warnings in tobacco retailers. This study is the first to evaluate the impact of such a policy in the USA. Methods: Cross-sectional street-intercept surveys conducted among adult current smokers and recent quitters before and after signage implementation assessed the awareness and impact of the signs. Approximately 10 street-intercept surveys were conducted at each of 50 tobacco retailers in New York City before and after policy implementation. A total of 1007 adults who were either current smokers or recent quitters were surveyed about the awareness and impact of tobacco health warning signs. Multivariate risk ratios (RR) were calculated to estimate awareness and impact of the signs. Results: Most participants (86%) were current smokers, and the sample was 28% African–American, 32% Hispanic/Latino and 27% non-Hispanic white. Awareness of tobacco health warning signs more than doubled after the policy implementation (adjusted RR =2.01, 95% CI 1.74 to 2.33). Signage posting was associated with an 11% increase in the extent to which signs made respondents think about quitting smoking (adjusted RR =1.11, 95% CI 1.01 to 1.22). Conclusions: A policy requiring tobacco retailers to display graphic health warning signs increased awareness of health risks of smoking and stimulated thoughts about quitting smoking. Additional research aimed at evaluating the effect of tobacco control measures in the retail environment is necessary to provide further rationale for implementing these changes.